A new past for a new nation? Historiography and politics in South Africa – A comparative approach (Historia, 2021)
The writing of history and the process of dealing with the past have always been influenced by social conditions and political transformations. Political changes have far-reaching consequences for the historical culture in the 'New South Africa'. An enlarged image of history fits into a political strategy of the 'Rainbow Nation', aiming to bring about a new national consensus and new political identities. Similar processes occur in European countries which underwent drastic political transformations. This article aims at a comparison between the historiographies and the politics of history in South Africa and Germany. The author describes trends in the development of historiography and mechanisms in political discourses but also wishes to warn against ideological over-simplifications and fruitless expectations.
Keywords: Historiography; South Africa; Wassenaar; Multiculturalism; Bilateral Conference Historians of the Netherlands and South Africa 2000; Liberal renewal; Language-use; Radical criticism